Patient Perspectives on the Financial Costs and Burdens of Breast Cancer Surgery. Issue 6 (June 2021) - Oshima, Sachiko M.; Tait, Sarah D.; Rushing, Christel; Lane, Whitney; Hyslop, Terry; Offodile, Anaeze C.; Wheeler, Stephanie B.; Zafar, S. Yousuf; Greenup, Rachel; Fish, Laura J.
Abstract : PURPOSE: Although financial toxicity is a well-documented aspect of cancer care, little is known about how patients narratively characterize financial experiences related to breast cancer treatment. We sought to examine these patient experiences through mixed methods analysis. METHODS: Women (≥ 18 years old) with a history of breast cancer were recruited from the Love Research Army and Sisters Network to complete an 88-item electronic survey including an open-ended response. Quantitative data were used to sort and stratify responses to the open-ended question, which comprised the qualitative data evaluated here. Descriptive statistics and qualitative content analysis were used to evaluate the financial costs and other burdens resulting from breast cancer surgery. RESULTS: In total, 511 respondents completed the survey in its entirety and wrote an open-ended response. Participants reported significant financial burden in different categories including direct payments for medical care and indirect costs such as lost wages and travel expenses. Treatment-related costs burdened participants for years after diagnosis, forming a financial arc for many participants. Discrepancies existed between the degree of financial burden reported on multiple-choice questions and participants' corresponding open-ended descriptions of financial burden. Participants described a lack of communication surrounding costs with their providers and difficulty negotiating payments with insurance. CONCLUSION: Breast cancer care can result in ongoing financial burden years after diagnosis among all patients, even those with adequate insurance patient populations.